Bibliometric Analysis of Studies on Urban Identity in Web of Science (WoS) Database - Murat Yeşil; Rabia Nurefşan Karabörk (Journal of Architectural Sciences and Applications)
In this study, it is aimed to examine the bibliometric characteristics of studies on urban identity and to determine the current situation. In this context, studies on ‘urban identity’ published in the Web of Science database between 1999 and 2024 were evaluated. Access to the database was provided on 08.03.2024 and bibliometric analysis of 2303 publications on the subject was carried out through the VOSviewer 1.6.20 program. In the research conducted, it was found that the most studies on the subject were published in 2020 (209); the studies were mostly in article type (1941); the studies were mostly conducted in the USA (397) and the UK (267) and the language of publication was predominantly English (2072); the most frequently repeated keywords in the published studies were place identity (514), place attachment (289), urban identity (151).